Genetic and Epigenetic Regulations of Tumor Progression and Metastasis - Smolkova, Bozena; Earl, Julie; Kataki, Agapi (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Genetic aberrations and epigenetic modifications are critical drivers of cancer progression and metastasis. Although recurrent mutations in primary and metastatic cancers have been shown to be concordant, there are several metastasis-associated mutations responsible for resistance to specific therapies that are frequently located in genes that regulate DNA methylation and chromatin modifications. Recent studies have shown that distinct subgroups of poor-prognosis tumors lack genetic alterations but are epigenetically regulated, pointing to the critical role of epigenetic modifications in cancer progression. This Special Issue provides novel insights into the mechanisms underlying processes associated with cancer cell plasticity and the development of metastatic disease.